Adapt or Perish: Women’s Resiliency in Tourism Village during the COVID-19 Pandemic in Nglanggeran - Wiwik Sushartami; Khusnul Bayu Aji; Herlambang Eka Persada (Universitas Andalas, 2024)
The growth of tourism villages is a central tenet of Indonesia’s tourism development policy. Nevertheless, based on the number of affected workers, the tourism village is one of the types of Indonesian tourist destinations hardest impacted by the COVID-19 pandemic. The pandemic has nearly entirely paralyzed the majority of tourism-related activities in the tourism village of Nglanggeran in Java. However, one unit has remained operational, namely Griya Cokelat, the women-led cocoa processing work unit. This study seeks to examine the situation of female workers in the tourism village during the pandemic, the capacity of women to acquire technology skills to bolster tourism resilience, and the impact of these activities on domestic relationships. The data collection included observing the working conditions of women in the tourism industry during the pandemic, conducting interviews with eleven informants, and examining pertinent literature. As a consequence of the COVID-19 pandemic, it was discovered that these women have had to learn more keenly how to use technology in order to shift their offline to online sales. Their technological adaptation has helped the tourism village’s resilience efforts. Women’s ability to use technology—in this example, the Internet—supports the change in gender roles in families.